2016
DOI: 10.1097/npt.0000000000000136
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Physical Therapy Techniques to Enhance Survival in Amyotrophic Lateral Sclerosis: A Systematic Review

Abstract: Specific pulmonary physical therapy interventions (IMT, LVRT, and MAC) have effectiveness in improving respiratory outcome measures and increasing survival. These should be routinely incorporated into the comprehensive management of individuals with ALS. More rigorous methodological investigations should be performed to replicate these findings.Video abstract available with brief technique demonstration of IMT and LVRT (see Supplemental Digital Content 1, http://links.lww.com/JNPT/A136).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Functional mobility may be targeted by providing appropriate mobility aids, such as canes, crutches, and walkers . Lung capacity may be improved by inspiratory muscle training (IMT) and lung volume recruitment training (LRVT) . Furthermore, helplessness and fatigue may be modified by teaching patients how to exert more control over the consequences of their disease by implementing a psychological intervention, such as cognitive behavioral therapy (CBT).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional mobility may be targeted by providing appropriate mobility aids, such as canes, crutches, and walkers . Lung capacity may be improved by inspiratory muscle training (IMT) and lung volume recruitment training (LRVT) . Furthermore, helplessness and fatigue may be modified by teaching patients how to exert more control over the consequences of their disease by implementing a psychological intervention, such as cognitive behavioral therapy (CBT).…”
Section: Discussionmentioning
confidence: 99%
“…7,29 Lung capacity may be improved by inspiratory muscle training (IMT) and lung volume recruitment training (LRVT). 45 Furthermore, helplessness and fatigue may be modified by teaching patients how to exert more control over the consequences of their disease by implementing a psychological intervention, such as cognitive behavioral therapy (CBT). CBT has already shown to improve helplessness and fatigue in patients with motor neuron disease and other chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Improving FVC, FEV 1 , MVV, MIP and MEP using respiratory training is already an established intervention in patients with a range of neuromuscular disorders [8,9], but is relatively new in neurodegenerative disorders. For example, lung volume-orientated training improves respiratory function tests such as FVC and peak cough expiratory flow in patients with amyotrophic lateral sclerosis [10]. Also, cut-off scores to determine when respiratory training is indicated are available for neuromuscular diseases, but are so far lacking for PD [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…IMT also shows benefits in other neurological populations, as in the study by Menezes et al (), who emphasize in their systematic review the respiratory muscle training in poststroke individuals, resulting in increased MIP and MEP, reducing respiratory complications. Macpherson et al (), in another systematic review, demonstrated that IMT improved respiratory muscle strength and FVC in individuals with ALS. In the study by Fry et al (), individuals with MS showed a significant improvement in MIP, FEV1, FVC, and FEF (forced expiratory flow) after IMT intervention, but there were no differences for MEP; thus, IMT increased significantly inspiratory muscle strength and resulted in a generalized improvement in the lung function.…”
Section: Discussionmentioning
confidence: 99%
“…Inzelberg et al (2005) observed improvement in inspiratory muscle strength and endurance and improvement in the perception of dyspnoea in individuals with PD after IMT. There are some studies in the literature evaluating IMT in populations with other neurological diseases, such as ischaemic stroke (Menezes et al, 2016), amyotrophic lateral sclerosis (ALS; Ferreira, Costa, Plentz, Coronel, & Sbruzzi, 2016;Macpherson, Bassile, & Clare, 2016) and multiple sclerosis (MS; Ferreira et al, 2016;Fry, Pfalzer, Chokshi, Wagner, & Jackson, 2007;Klefbeck & Nedjad, 2003), which showed improvement in muscular strength and respiratory function. However, in addition to these, other benefits can be verified in other diseases, such as heart failure (Caruso et al, 2016;Mello et al, 2012) and chronic obstructive pulmonary disease (Basso-Vanelli et al, 2016), in which IMT was able to improve thoracic mobility, increase functional capacity, besides autonomic and peripheral controls, and quality of life.…”
mentioning
confidence: 99%